Improving 21st Century Students' Learning Skills through the Group Investigation Cooperative Learning Model in Arabic Classes - Sarif, Suharia; Yasmadi, Yasmadi; Jundi, Muhammad; Fitri, Titi; Haerullah, Ira Safira; Hasibuan, Renni; Gustian, Nabil (UIN Sunan Gunung Djati Bandung, 2024)
This study explores the Group Investigation (GI) model's role in developing 21st-century skills in collaboration, communication, creativity, and problem-solving in Arabic language learning. Addressing a research gap, it examines how GI enhances these skills, fostering effective learning and student engagement in the classroom. This study uses a qualitative approach, and it examines the implementation of the Group Investigation model in teaching Arabic to 57 students in two classes. Observations over 3 hours per class focused on student interactions during group assignments, highlighting activeness, role distribution, opinion exchange, and task allocation. Documentation through photos and videos validated the observations and supported the analysis of 21st-century skills. Data analysis employed an interactive approach. The results of the study indicate that the implementation of the Group Investigation cooperative learning model in Arabic learning instruction significantly illustrates students' 21st-century skills. This study contributes to Arabic language learning by demonstrating that the Group Investigation (GI) model enhances 21st-century skills, particularly creativity. Future research should explore additional strategies within GI to strengthen communication and collaboration while evaluating its impact on Arabic language learning outcomes.